A Discussion of Speaking Our Minds by Thom Scott-Phillips - Deriu, Valentina (Theoria et Historia Scientiarum, 2019)
Abstract. This discussion aims to investigate some claims proposed by Scott-Phillips in Speaking our minds. The main thesis by this book is that ostensive-inferential communication is the prerogative of human beings. In fact, despite admitting a continuity between human beings and other animals at the level of cognitive architectures, Scott-Phillips places a discontinuity at the communicative level. In his view, human communication requires high-order mental metarepresentations, guaranteed by a sophisticated mindreading system that, in his opinion, is not present in nonhuman primates. Recently, this idea has been challenged by some scholars. The aim of the present discussion is to take into account this debate.